Інтермедіальна інтерпретація ключових тем метафізичної поезії (на прикладі артпроєкту «Море — тут. Відсутність як присутність») - Рязанцева, Т. (Слово і Час, 2023)
На матеріалі двох фотопоетичних розділів міжнародного мультимедійного артпроєкту «Море — тут. Відсутність як присутність»
(2020) розглянуто особливості новітніх творчих підходів до розробки традиційних тем метафізичної поезії (стосунки людини з Богом,
смерть і час). Окреслено ключові характеристики метафізичної поезії та фотопоезії, притаманні їм типи інтермедіальних взаємодій.
З’ясовано, що застосування інтермедіальних стратегій демонструє
життєздатність усталених тематичних потрактувань і виявляє
елементи новаторства, а також відповідає провідній стилістичній
тенденції метафізичної поезії — економити засоби вираження у прагненні сягнути найвищого рівня динаміки і драматичної напруги. The paper discusses the productivity of the new creative approaches to the established
types of poetry.
Building on the theoretical definitions, taxonomies, and observations formulated in
the works of James Smith, Frank Warnke, Michael Nott, Robert Crawford and Norman
McBeath, Susan Sontag, Viktoria Khoniu, et al., the research argues that the artistic practices
of photopoetry (“a form of photo-text that takes, for its primary components, poetry
and photography”, Michael Nott) offer new ways to interpret certain topics of metaphysical
poetry. The term “metaphysical poetry” defines an independent trend of literature focused
on “the realities of peculiar kind” (James Smith) such as Time, Death, Religion, and Love.
The material for analysis is taken from the international multimedia project “The
Sea Is Here: Absence as Presence” (2020) edited by Natalia Kutsepova (USA) and Nina
Kharchenko (Germany). Two photopoetic pieces from this art book, “Miracles” by Shaun
Evans and “Bond” by Kati Dahlmann, explore the themes of Religion and Death, which
are central to metaphysical poetry.
The detailed analysis of “Miracles” and “Bond” outlines the types of artistic collaboration
in both projects and focuses on their structural, stylistic, and semantic characteristics.
Special attention is paid to the ways of interaction between photographs and texts. It
is noted that the principle of photopoetic imagery is close to the principle of metaphysical
conceit (to harmonize the incompatible).
The author concludes that the creative strategy of photopoetry can be instrumental
in interpreting the key metaphysical topics. It proves the vitality of some traditional
concepts (memory as a tool to transform the transient/mortal into the stable/immortal)
and introduces important innovations (the detached position of a human being in their
communication with God).